Malaysian image of two U.S. leaders: Obama and Trump - Syed Abdullah Idid, Syed Arabi (2018)
Studying how citizens of a country view another world leader has often been conducted by international polling agencies. In many of these studies, the views of Malaysians were often not solicited due to reasons best known to these agencies. It is the objective of this paper to see how Malaysians view two world leaders at two periods of time namely how Malaysians viewed the performance of the leadership, one the present President, Donald Trump and that of his predecessor, Barack Obama. A nationwide study was made on these two personalities. Malaysian perceptions were based on how they felt the two presidents dealt with the Palestinian issue and the world economic problems. The present paper will present findings on the perception of Malaysians toward Barack Obama based on the surveys in 2010 and 2013 with 1,367 and 1,439 respondents and another two studies on Donald Trump in 2017 and in 2018 with 1,326 and 2,061 respondents respectively.